Pendidikan Islam, Perubahan Sosial, dan Pembangunan di Indonesia - Tabi'in, As'adut; Hasibuan, Lias; US, Kasful Anwar (Asatiza: Jurnal Pendidikan, 2022)
This study aimed at determining how the implementation of Islamic education, describing the social changes and contribution to the development of Indonesia. This research was descriptive qualitative research using the library method. This study reveals several facts that the trend of understanding transnational Islam brought by several Indonesian students from the Middle East. The practice tends to become a conflict with Islamic values that Rahmatan Lil 'Alamin, participated in social change in Indonesia. Then it was also driven by the high religious spirit of young people without being equipped with qualified knowledge, strengthening them in taking a stand. This became one of the causes of the formation of perspectives, attitudes, and decisions to all conditions that exist in the environment